Advancing in vitro vascular wall modelling using digital light processing to study hyperglycemia-driven cell changes - Pokholenko, Ianina; Meeremans, Marguerite; Van Vlierberghe, Sandra; Pien, Nele; De Schauwer, Catharina (Frontiers in Bioengineering and Biotechnology, 2026)
BackgroundMetabolic syndrome is a pathological state, frequently associated with type 2 diabetes, which is marked by abdominal obesity, impaired insulin action, hypertension, and vascular wall changes. Similar to humans, horses can suffer from equine metabolic syndrome. A representative in vitro vascular wall model is needed to study its pathophysiology and develop novel treatments for both human and equine patients.MethodsIn this study, scaffolds manufactured via digital light processing (DLP) exploiting an acrylate-endcapped urethane-based polymer precursor with a polyethylene glycol backbone (AUP2PEG) were coated with collagen or gelatin derivatives. Their cell-interactive properties were evaluated using equine mesenchymal stromal cells (MSC) and endothelial cells (EC). Coating was performed using either UV-induced photopolymerization of gelatin methacryloyl (GelMA) on the surface of the DLP-printed scaffold or physisorption of type I atelocollagen.ResultsThe GelMA coating formed a thin, uniform layer on the scaffold surface and improved the cytocompatibility of DLP-printed AUP2PEG-based scaffolds for EC and MSC. Furthermore, they permitted MSC trilineage differentiation. To mimic the endothelial damage occurring in metabolic syndrome conditions, the GelMA-coated AUP2PEG scaffolds were incubated in high glucose culture conditions. Short-term cell culture in these conditions significantly reduced the number of viable EC. In contrast, the short-term culture of MSC in these conditions did not result in a similarly deleterious impact on cell viability.ConclusionIn conclusion, GelMA-coated DLP-printed AUP2PEG scaffolds facilitate the growth of EC and MSC. Furthermore, exposing EC cultured on the developed scaffolds to hyperglycemic culture conditions negatively affects the viability of EC, comparable to what is observed in two-dimensional culture conditions.